CAPACITY BUILDING FOR FEMALE VOLUNTEERS: SRIKANDI OF EAST JAVA IN DISASTER PREPAREDNESS EFFORTS, CARDIAC ARREST FIRST AID WITH CPR - Dini Prastyo Wijayanti, S.Kep.Ns., M.Kep; Nisa Dewanti; Tamara Nur Budiarti; Kiki Widyasari; Nurul Kusuma (Community Service Journal of Indonesia, 2023)
The importance and influence of female volunteerism Srikandi East Java in disaster relief is widely recognized to respond disaster preparedness. Cardiopulmonary resuscitation (CPR) performed by bystanders is an essential treatment for sudden cardiac arrest. Cardiopulmonary Resuscitation is an emergency lifesaving procedure performed when the heart stops beating. The aim of community service is to improving knowledge and skills of CPR to female volunteers Srikandi East Java confidence to help their families, communities and people in need during disasters and emergencies. The method used in this community service activity is to provide training CPR and councelling cardiac arrest . This activity was carried out may 2023 which was attended by 80 female volunteers member of Srikandi East Java. The results show that the activity has achieved success according to the success indicators that have been set, namely as many as 80 female volunteers member of Srikandi East Java attendance is 100%, participants participate in activities enthusiastically, knowledge of CPR after training and counseling increases significantly. CPR drills should be done regularly so that many female bystanders are trained.